Self-Disclosure of Students with Minangkabau and Batak Cultural Backgrounds - Tati Ayuni; Herman Nirwana; Netrawati Netrawati (Universitas Negeri Padang, 2020)
The expression is derived from the Minangkabau and Batak Toba cultures. This study aims to describe the self-disclosure of high school students in terms of Minangkabau and Batak Toba culture. The sample used in this study were 329 high school students consisting of 165 students with a Minangkabau cultural background and 164 students with a Toba Batak culture background. This research uses Proportional Random Sampling technique. The instrument used in this study was a system Self Disclosure Skala with a reliability of 0.91029. The data analysis used in this research is ANOVA (Analysis Of Variants). there is no difference in the self-disclosure of students with Minangkabau cultural backgrounds between men and women. There is no difference in the self-disclosure of students with Batak cultural backgrounds between boys and girls.There are differences in the self-disclosure of students with Minangkabau and Batak cultural backgrounds in terms of male gender. There are differences in students' self-disclosure with Minangkabau and Batak cultural backgrounds which are reviewed based on the gender of the women.